Practical linear algebra a geometry toolbox - Farin, Gerald E.; Hansford, Dianne (Boca Raton, FL CRC Press, 2014)
"Practical Linear Algebra covers all the concepts in a traditional undergraduate-level linear algebra course, but with a focus on practical applications. The book develops these fundamental concepts in 2D and 3D with a strong emphasis on geometric understanding before presenting the general (n-dimensional) concept. The book does not employ a theorem/proof structure, and it spends very little time on tedious, by-hand calculations (e.g., reduction to row-echelon form), which in most job applications are performed by products such as Mathematica. Instead the book presents concepts through examples and applications. "-- Provided by publisher.
Prof. Lawlita N. Cabahug (Recommending faculty) : BS Mathematics Program
Includes bibliographical references and index.
Keywords: Algebras, Linear -- Study and teaching; Geometry, Analytic -- Study and teaching; Linear operators